From dance bands to radio and records: Pop music promotion in West Germany and the decline of the Schlager genre, 1945–1964 - Nathaus, Klaus (Popular Music History, 2012)
This article traces key developments in the production and promotion of popular music in West Germany during the twenty years after the Second World War. Starting from the observation that performance royalties were a relatively important source of revenue from music, the article first describes how, around 1950, dance bands became the principal gatekeepers, before looking at the impact of radio and records on the musical production system. It shows that this structural change led to a marked concentration of the music business and argues that the immediate effect on the popular repertoire was moderate. The most consequential change was a widespread condemnation of Schlager and a growing sense of detachment from this genre among songwriters, which set the path for the further decline of this musical style in subsequent decades.